2014
DOI: 10.1038/ngeo2253
|View full text |Cite
|
Sign up to set email alerts
|

Atmospheric circulation as a source of uncertainty in climate change projections

Abstract: As the evidence for anthropogenic climate change continues to strengthen and 5 concerns about severe weather events increase, scientific interest is rapidly 6 shifting from detection and attribution of global climate change to prediction 7 of its impacts at the regional scale. However, pretty much everything we have 8 any confidence in when it comes to climate change is related to global patterns 9 of surface temperature, which are primarily controlled by thermodynamics. In 10 contrast, we have much less confi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

11
670
0
4

Year Published

2015
2015
2017
2017

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 816 publications
(685 citation statements)
references
References 44 publications
11
670
0
4
Order By: Relevance
“…This is a further motivation to extend these techniques to geophysical extremes. Interestingly, the high sensitivity of extremes in the vicinity of tipping points suggests that observing unusual return times for extreme weather events may provide a flag signalling at an an early stage qualitative changes of atmospheric circulation, which could hardly be predicted by looking at the bulk of the statistics; see also [319]. …”
Section: Discussionmentioning
confidence: 99%
“…This is a further motivation to extend these techniques to geophysical extremes. Interestingly, the high sensitivity of extremes in the vicinity of tipping points suggests that observing unusual return times for extreme weather events may provide a flag signalling at an an early stage qualitative changes of atmospheric circulation, which could hardly be predicted by looking at the bulk of the statistics; see also [319]. …”
Section: Discussionmentioning
confidence: 99%
“…The authors then partitioned observed changes in temperature extremes into those associated with changes in the occurrence of circulation regimes (dynamic changes) and those that have no such association (thermodynamic changes). This kind of partitioning is a growing theme in climate science 8 . Horton and colleagues find that most regions have experienced a clear increase in summertime high temperature extremes since 1979.…”
Section: T H E O D O R E G S H E P H E R Dmentioning
confidence: 99%
“…To the extent this internal variability is unpredictable, the resultant uncertainty is irreducible. This "single realization effect" is large enough to mask the forced regional response, presenting a major challenge for understanding and communication of regional climate change 45,82 .…”
Section: Effects Of Internal Variabilitymentioning
confidence: 99%